An analysis of Tesla’s market competitiveness using the SWOT-PEST analysis: (TESLA: Transnational Ecosystem Laboratory and Actions) - Barrie, Gibrilla (Вестник Томского государственного университета. Экономика)
According to J.B. Straubel, Martin Eberhard, Marc Tarpenning, and Ian Wright, the Transnational Ecosystem Laboratory and Actions (TESLA, Tesla) was established in 2003. Nevertheless, Elon Musk attained leadership as the company’s CEO in 2004 and, with the most significant financial investment of U.S. $ 6.5 million in 2008, sought to be a fundamental contributor to the sustainable protection of current and future society through their effort in extreme innovative research and development in electric automobiles and sustainable energy. This paper seeks to analyze Tesla’s market competitiveness in the global market using the SWOT-PEST to understand the exogenous and endogenous circumstances surrounding its growth and vulnerability. Therefore, the analysis is the most critical tool employed to strengthen and protect its capacity and competitiveness in its current and future market environments. Its sustainable growth can be achieved through established strategies surrounding its market leadership, competitors, new entrants, production and sales rate, and the significance of its position towards the changing technological and market demand trend. From the analysis, the study discovers that there is a significant step that Tesla must employ in their current strategies for market growth and sustainability. There must be an extensive product line with efficiency, effectiveness, and fewer mechanical complications to meet the increasing demand of the electric vehicle market. They must also strengthen their influence and control in current markets such as China and expand their production and sales in the untapped market such as India, Brazil, and Africa with friendly and affordable pricing, and, most importantly, maintain consistency with uniqueness in their production as against their competitors for long term leadership.